Faktor-faktor yang memengaruhi penghindaran pajak pada perusahaan manufaktur di bursa efek Indonesia - DEANNA PUSPITA; MEIRISKA FEBRIANTI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to examine the influence of firm size, return on asset, leverage, capital intensity, sales growth and composition of the independent board to tax avoidance. The population of this research is all manufactured companies listed in Indonesia Stock Exchange from 2012 to 2014. Samples are obtained through purposive sampling method, in which only 52 of listed manufactured companies in Indonesia Stock Exchange meet the sampling criterias resulting 156 data available are taken as the samples. The research resource are taken from Indonesia Stock Exchange website. This research used multiple regression method to test the effect of each variable in influencing tax avoidance. The empirical result indicates that firm size, return on asset and sales growth have influence to tax avoidance. However leverage, capital intensity and composition of the independent board have no influence to tax avoidance.